The Effects of Concrete-Objective Information Program on Pre-operative Anxiety in Abdominal Surgery Patients - Thuchart, Siwaporn; Asdornwised, Usavadee; Pinyopasakul, Wanpen; Trakarnsanga, Auttaporn (Nursing Science Journal of Thailand, 2019)
Purpose: The aim of this study was to study the effects of concrete-objective information program on preoperative anxiety in abdominal surgery patients. Design: A quasi-experimental research (two group pre-posttest design). Methods: The sample consisted of 62 preoperative abdominal surgery patients. They were divided into two groups, the experimental and control groups. Thirty-one participants were included in each group. The experimental group was received the concrete-objective information via video and usual nursing care while the control group was received only usual nursing care. Data were collected using a demographic data record form and Visual Analog Scale–Anxiety (VAS-A) assessment form. The patients’ anxiety was assessed before receiving the program and twice after the program (immediately and on the day of surgery in the waiting room). Data were analyzed using Mann-Whitney U Test and Wilcoxon Signed-Rank Test statistical package. Main findings: The results showed that on the day of surgery in the waiting room (posttest 2) patients who received a concrete–objective information via video had statistically lower mean scores of anxiety than those who received usual nursing care (p = .017). In addition, the anxiety mean scores in the experimental group immediately after receiving the program (posttest 1) was statistically lower than that before receiving the program (p = .001). Conclusions and recommendations: Concrete-objective information program could reduce pre-operative anxiety in abdominal surgery patients. This program should be used to decrease the anxiety level during pre-operative period.